ECOBRICKS, DAUR ULANG SAMPAH PLASTIK SEBAGAI RINTISAN ECOPRENEURSHIP - LV. Ratna Devi Sakuntalawati; Irsyadul Ibad (Jurnal Kewirausahaan dan Bisnis, 2021)
Sejahtera Waste Bank is a waste bank located in 5th hamlet, Joyotakan Village, Serengan District, Surakarta City. Household waste management activities in this waste bank are still limited to collecting, sorting, weighing, recording, and selling. Plastic waste is one of the most common types of household waste, but most of it is only sold to collectors. It shows that the management of plastic waste into creative products has not been developed. In fact, if it becomes a creative product, it will increase the economic value of the plastic waste. Therefore, the Waste Bank is given training and assistance for creative products in the form of creative product materials with ecobricks technology and creative product marketing. As a result, partners are able to process plastic waste into material which is then created into creative products in the form of stool and table furniture sets. In addition, this product is capable of absorbing approximately 25 kg of plastic waste, so using ecobricks technology is very suitable for reducing piles of plastic waste generated by households. For the sustainability of the waste bank business activities, assistance is carried out from the beginning to the end of the community partnership program. It is intended that the waste bank can function as a center for activities that become a place for businesses whose activities include recycling plastic waste into creative products. This activity can be an ecopreneurship pilot that is expected to meet market demand and increase people's income.Keywords: waste bank, plastic waste, ecobricks, stool, ecopreneurship